Communication and health in a multi-ethnic society - Robinson, Mark ca. 20./21. Jh (Policy Press, 2002)
This book provides a rigorous and challenging review of recent research in the realms of communication and cultural diversity. Focusing on health communication interventions concerning service users who may lack fluency in English, it shows that meeting the needs of all health service users depends on both structures and processes of communication